The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1179/009346909791070862
|View full text |Cite
|
Sign up to set email alerts
|

Middle Palaeolithic Lithic Technology from the Western High Desert of Egypt

Abstract: Recent work in the high desert west of Abydos in Egypt has focused on the Middle Palaeolithic technologies known as Nubian 1 and 2 types and classicLevallois) which are abundant and are found in virtually all stages of production. Although these were originally defined and treated as three discrete technologies) refitting and quantitative analyses show that they are variants of one technology. While this has direct implications for interpreting lithic technological variability in this region) the demonstration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 4 publications
3
32
1
Order By: Relevance
“…Chiotti et al [67] offer an alternative perspective to Nubian core typology (Type 1 and Type 2). Using refittings and quantitative analysis, the authors show how the Nubian Type 1, Type 2 and ‘classical centripetal’ Levallois cores may represent separate stages within a continuous centripetal Levallois reduction.…”
Section: Lithic Technological Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Chiotti et al [67] offer an alternative perspective to Nubian core typology (Type 1 and Type 2). Using refittings and quantitative analysis, the authors show how the Nubian Type 1, Type 2 and ‘classical centripetal’ Levallois cores may represent separate stages within a continuous centripetal Levallois reduction.…”
Section: Lithic Technological Analysismentioning
confidence: 99%
“…Using refittings and quantitative analysis, the authors show how the Nubian Type 1, Type 2 and ‘classical centripetal’ Levallois cores may represent separate stages within a continuous centripetal Levallois reduction. Indeed, Chiotti et al [67] propose that by removing the distal portion of a Nubian core, such differences are muted. At this point the authors refer to van Peer [70] who coined the term ‘Safaha Method’, which describes an additional step in the Nubian preparation schema identified at Nazlet Safaha 1 and 2.…”
Section: Lithic Technological Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The Nubian technology is a specific variant of the Levallois technology (GoderGoldberger et al 2016, Guichard & Guichard 19651968;Usik et al 2013;Van Peer 1992) found within Middle Paleolithic techno-complexes at surface sites across the western High Desert in Egypt (Chiotti et al 2009;Olszewski et al 2005), the central Negev highlands (Goder-Goldberger et al 2016) and Arabia (Crassard & Hilbert 2013;Hilbert et al 2016;Rose et al 2011;Usik et al 2013). Common to these finds is a technological package composed of the Levallois Nubian technology alongside both Levallois centripetal and bidirectional modes of production.…”
Section: Introductionmentioning
confidence: 99%